The influence of age, playing position, anthropometry and fitness on career attainment outcomes in rugby league. Issue 13 (2nd July 2016) - Till, Kevin; Cobley, Steve; Morley, David; O'hara, John; Chapman, Chris; Cooke, Carlton
ABSTRACT: This study evaluated the influence of annual-age category, relative age, playing position, anthropometry and fitness on the career attainment outcomes of junior rugby league players originally selected for a talent identification and development (TID) programme. Junior rugby league players ( N = 580) were grouped retrospectively according to their career attainment level (i.e., amateur, academy and professional). Anthropometric (height, sitting height, body mass, sum of four skinfolds), maturational (age at peak height velocity; PHV) and fitness (power, speed, change of direction speed, estimated ) characteristics were assessed at the Under 13s, 14s and 15s annual-age categories. Relative age (Q2 = 8.5% vs. Q4 = 25.5%) and playing position (Pivots = 19.5% vs. Props = 5.8%) influenced the percentage of players attaining professional status. Anthropometry and fitness had a significant effect on career attainment at the Under 14 ( P = 0.002, η 2 = 0.16) and 15 ( P = 0.01, η 2 = 0.12) annual-age categories. Findings at the Under 14s showed future professional players were significantly later maturing compared to academy and amateur players. Findings suggest that relative age, playing position, anthropometry and fitness can influence the career attainment of junior rugby league players. TID programmes within rugby league, and other related team sports, should be aware and acknowledge the factors influencing long-term career attainment, and not delimit development opportunities during early adolescence.